Pelatihan Pengelolaan Keuangan Keluarga Para Tenaga Pendidik dan Tenaga Kependidikan dalam Rangka Meningkatkan Literasi Keuangan di RA Alkhairaat Duyu - Nanang Qosim; Nurapiah, Nurapiah; Rukhayati, Rukhayati; Abdul Wahab (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
Family financial management is a crucial aspect in realizing economic welfare, especially for educators and education personnel who often have limited income. Therefore, this service activity aims to improve the financial literacy of educators and education personnel at RA Alkhairaat Duyu through effective and applicable family financial management training. The methods used in this activity include lectures, tutorials (mentoring), interactive discussions, and evaluation with pre-test and post-test to measure the level of understanding of participants before and after training. In the implementation of the activities, the materials presented included family budget planning, wise debt management, and the importance of saving and investing for the future. In addition, participants also gained skills in conducting simple financial records, which can help them allocate their income more effectively and efficiently. The results of this training showed an increase in participants' understanding, especially in terms of budget management, debt, and saving and investing. The program also produced a training module that can be used for future reference, an evaluation report, and easy-to-understand educational media. With this program, it is hoped that educators and education personnel can implement better financial management strategies, so that they can achieve more secure and sustainable family economic stability.